Influence of induced diabetes mellitus on hormonal profile of Lewis lung carcinoma in BALB/c Nude mice - E. M. Frantsiyants; V. A. Bandovkina; I. V. Kaplieva; A. I. Shikhlyarova; E. I. Surikova; I. V. Neskubina; Yu. A. Pogorelova; L. K. Trepitaki; N. D. Cheryarina (Южно-Российский онкологический журнал, 2023)
Purpose of the study. The assessment of diabetes mellitus (DM) effect on levels of sex hormones in tumor and peritumoral tissues in BALB/c Nude mice with Lewis lung carcinoma (LLC).Materials and methods. The study included 42 male and female BALB/c Nude mice aged 8–9 weeks weighing 21–22 g. Alloxan-induced DM was reproduced in mice of the main group, and then LLC was transplanted. Levels of estrone (E1), estradiol (E2), testosterone (T), progesterone (P4) and prolactin (PRL), as well as steroid hormone receptors: estrogens (REα, REβ), androgens (RA), and progesterone (RP4) were measured by RIA and ELISA in samples of tumor and peritumoral tissues. Animals with LLC without DM were used as controls. The statistical analysis was performed using the Statistica 10 program; differences were considered significant at p < 0.05.Results. DM in males was reproduced only after a double injection of alloxan, and was characterized by lower blood glucose levels compared to females. The growth of LLC in animals with alloxan-induced DM was possible only in female BALB/c Nude mice; in BALB/c Nude males, the tumor could not be transplanted either independently or in combination with DM. Females in the main group showed greater average tumor volumes throughout the experiment and reduced survival, compared to the control group. Tumor samples from females with LLC+DM were more saturated with sex steroids, but depleted in steroid hormone receptors, which probably contributed to the ability to avoid the body's regulatory signals.Conclusion. The growth of LLC in presence of induced DM was sex-dependent, since the tumor could not be transplanted to male mice. DM affected the levels of sex steroids and their receptors tumor tissues in female BALB/c Nude mice.